Money, barter and inflation in Russia - Byung-Yeon Kim; Jukka Pirttilä; Jouko Rautava (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
Using a macroeconometric framework, this paper analyses relationships among money, barter and inflation in Russia during the transition period.Following the development of a theoretical framework that introduces barter in a standard small open economy macro model, we estimate our model using structural cointegration and vector error correction methods.Our findings suggest that barter has resulted partly from output losses and partly from a reduction in real money balances, but to a lesser extent.There is some evidence that the effect of barter on prices is less than that of money.We also find that increases in barter are affected by banking failure.Our results imply that a macro model that excludes barter fails to capture all the relevant information for inference on money and inflation in Russia.
URN:NBN:fi:bof-201408072129
Keywords: 330